The Palace of Sargon, King of Assyria. Monumental Wall Reliefs at Dur-Sharrukin, from Original Drawings Made at the Time of their Discovery in 1843-1844 by Botta and Flandin / Le palais de Sargon d'Assyrie. Étude des reliefs de Dur Sharrukin d'après les dessins exécutés au mоment de leur découverte en 1843-1844 par Botta et Flandin - Albenda, Pauline (1986)
p. 107-114: The Epigraphs, by Christopher ?. F. Walker; p. 271-278: Les inscriptions, par Christopher C. F. Walker